Giving offense essays on censorship - Coetzee, J. M. 1940- (Univ. of Chicago Press, 1996)
From Osip Mandelstam commanded to compose an ode in praise of Stalin, to Breyten Breytenbach writing poems under and for the eyes of his prison guards, to Aleksandr Solzhenitsyn engaging in a trial of wits with the organs of the Soviet state, Giving Offense focuses on the ways authors have historically responded to censorship. It also analyzes the arguments of Catharine MacKinnon for the suppression of pornography and traces the operations of the old South African censorship system. Finally, Coetzee delves into the early history of apartheid and critizes the blankness of contemporary political science in its efforts to address the deeper motives behind apartheid